A Sociolinguistic Study of Code-Switching Types in Cinta Laura’s Speech n The Youtube Channel Suara Berkelas - Fransisca Stevany Br Pakpahan; Afriana (IKIP Siliwangi, 2026)
This study is a descriptive qualitative research that analyze the types of code-switching used in the speech of Cinta Laura Kiehl on the YouTube channel Suara Berkelas. The study uses Poplack’s (1980) classification, which includes inter-sentential, intra-sentential, and tag switching. The data was collected through observational method and transcription techniques from a selected video. Meanwhile the data analysis using distributional method and immediate constituent analysis technique which involves breaking down utterances into their structural components. The findings reveal that three types of code-switching are present in the data. Intra-sentential type is the most dominant type, with 17 occurrences (43.6%), followed by tag switching with 12 occurrences (30.8%), and inter-sentential switching with 10 occurrences (25.6%). The frequent use of intra-sentential switching reflects the speaker’s bilingual ability in combining two languages within one sentence. In addition, tag switching is used to support interaction, while inter-sentential switching helps organize ideas more clearly. This study discusses the use of code-switching in digital media communication, especially in bilingual public figures.